Pengaruh Pemanfaatan Sistem Informasi Akuntansi, Pengendalian Internal Dan Pemahaman Akuntansi Terhadap Kualitas Laporan Keuangan Pada Koperasi Simpan Pinjam Di Kecamatan Karangasem - Dwi Widhiantari, Ida Ayu; Dewi Padnyawati, Kadek (UNHI Press, 2025)
The quality of financial reports in a Cooperative is very important for the suitability of the contents of the financial report with the cooperative's accountability report to its members. So it is important during the preparation of financial reports to ensure quality, it is necessary to utilize the accounting information system properly, improve internal control in the cooperative and cooperative employees must have a good understanding of accounting. This study aims to determine the effect of the use of accounting information systems, internal control and accounting understanding on the quality of financial reports in Savings and Loan Cooperatives in Karangasem District. The number of samples in this study was 78 respondents who were determined by purposive sampling technique and tested using multiple linear regression analysis techniques using the SPSS Version 24.0 for Windows application. The results of this study are that the Accounting Information System, Internal Control, and Accounting Understanding have a positive and significant effect on the Quality of Financial Reports.